Systemic Levels of CCL2, CCL3, CCL4 and CXCL8 Differ According to Age, Time Period and Season among Children Newly Diagnosed with type 1 Diabetes and their Healthy Siblings. (December 2014) - Thorsen, S. U.; Eising, S.; Mortensen, H. B.; Skogstrand, K.; Pociot, F.; Johannesen, J.; Svensson, J.; the Danish Childhood Diabetes Registry
Abstract The mechanisms by which antigen‐specific T cells migrate to the islets of Langerhans in type 1 diabetes (T1D) are largely unknown. Chemokines attract immune cells to sites of inflammation. The aim was to elucidate the role of inflammatory chemokines in T1D at time of diagnosis. From a population‐based registry of children diagnosed with T1D from 1997 to 2005, we studied five different inflammatory chemokines (CCL2, CCL3, CCL4, CCL5 and CXCL8). Four hundred and eighty‐two cases and 479 sibling frequencies matched on age and sample year distribution were included. Patients showed lower levels of CCL4 compared to siblings, but this result was not significant after correction for multiple testing. CCL2, CCL3, CCL4 and CXCL8 levels were highest in the most recent cohorts (P < 0.01) in both patients and siblings. A significant seasonal variation – for most of the chemokines – was demonstrated with the highest level during the summer period in both patients and siblings. In addition, there was a significant inverse relationship between CCL4 levels and age. When comparing patients and siblings, remarkably few differences were identified, but interestingly chemokine levels varied with age, season and period for the entire study population. Such variations should be taken into account when studying chemokines in paediatric populations.